What’s holding back private sector agricultural insurance? - Hazell, Peter B. R.; Timu, Anne G. (International Food Policy Research Institute, 2024)
Much of the recent literature on agricultural insurance focuses on ways to increase farmers’ demand for insurance, but this paper revisits the supply side of the insurance market. To better understand the conditions under which private insurance has been successful or failed the paper draws on the available empirical and theoretical literature, on case studies, and interviews with selected insurers. While there are many examples of innovative solutions to some of the product design, marketing and delivery challenges facing agricultural insurance, our review suggests that private unsubsidized insurance can only play a limited role in terms of the overall risk management needs of agriculture. Fundamentally, agricultural insurance can only address certain types of risks, and these are often not the most important from the farmers’ perspective. For most farmers insurance is best seen as part of a broader risk management approach, and its relevance for commercial farmers linked to value chains can be quite different from that for more subsistence-oriented smallholders. Commercial farmers generally have the most options for managing risk and may benefit most from specific types of indemnity or index-based products to protect specific agricultural investments and there are many examples of insurers meeting this need on an affordable and unsubsidized basis. On the other hand, subsistence-oriented farmers, especially poor and vulnerable ones, need insurance that can help protect their household income and consumption from negative shocks. This kind of insurance is expensive and difficult to supply without subsidies and requires strong public sector support. Even if targeted in this way, private unsubsidized insurance will only thrive given a supporting policy environment and, to keep costs down and improve the relevance and delivery of its products, insurers need to take full advantage of new and emerging digital and remote sensing innovations, and where possible, partner with intermediaries who can bundle their insurance with credit, farm inputs and other services.